Pendidikan Kewargaan Negara - Munadi Munadi (Resolusi: Jurnal Sosial Politik, 2020)
The study on the State Citizenship Education has experienced the development of discourse by experts, especially in political science and education science. In the democratic system, one's personality is still valued as something unique or specific. That is why there is a statement that mentions differences of opinion are still valued as diversity. In the State Citizenship Education, this discussion on personality provides an understanding of the main importance of person in the democratic system and everyone tries to play a role in it as a citizen who has the rights and obligations as appropriate as possible. This paper underlines that, behavioral and political science that use the basis of functional thinking and systems approach can be utilized by the State Citizenship Education to understand the use of citizens' rights and obligations in the society.